The G20 countries should engage with blockchain technologies to build an inclusive, transparent, and accountable digital economy for all - Julie Maupin (Kiel Institute for the World Economy (IfW), 2017)
Blockchain technologies hold the key to building an inclusive global digital economy that is auditably secure and transparently accountable to the world's citizens. At a time when governments must fight to restore the public's faith in cross-border economic cooperation, blockchains can play a critical role in strengthening economic resilience while ensuring the global economy works to the benefit of all. The G20 must take decisive steps to harness this technology in service of its policy goals across the core focus areas of economic resilience, financial inclusion, taxation, trade and investment, employment, climate, health, sustainable development, and women's empowerment. Failure to do so risks further fragmenting the global economy, undermining public trust in international economic institutions, and pushing the most cutting-edge blockchain developments into dark web deployments that are beyond the reach of government influence. By acting now to embrace blockchains' socially beneficial properties and minimize their potential downside risks, the G20 governments can lay the foundation for a just, prosperous, and truly shared global economy.
Keywords: E42; E58; F33; G15; K24; K33; O33; Q56; 330; blockchain; distributed ledger; tangle; cryptocurrency; Bitcoin; Ethereum; G20; WTO; Basel Agreements; Paris Agreement; international law; regulation; technology; innovation; transnational cooperation; trade; environment; financial system; monetary system